Open online course for prepare world teachers - Daradkeh, Y. I.; Kukharenko, V. M. (My University, 2016)
The purpose is to display that the use of a system approach in a working up the development of distance learning systems, open online courses, blended (hybrid) training teachers who have the content curator experience and secures an achievement of a high-quality education. The analysis results show that distance education technologies leave you to create and use a variety of methods and technological devices of training that meet the requirements of the customer training, promote student motivation and training of teachers, as well as personalizing the learning process. It is important that the strategy of various distance learning technologies have been supported by educational purposes and based on effective organizational support model.
Keywords: distance learning; blended (hybrid) learning quality; MOOC; flipped class; content curator